Kritik Formalistik Lukisan Berjudul “The Wounded Deer” Karya Frida Kahlo - Azie, Nanda Safiira; Prasetyo, Abdul Rahman (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2024)
The Wounded Deer is one of the paintings belonging to the famous Mexican painter, Frida Kahlo. Frida Kahlo is famous for her unique paintings that have their own characteristics. The painting The Wounded Deer uses a flow of imaginary surrealism. Surrealism is a combination of dreams and reality which makes real objects look like they are in a dream. The painting has its own meaning that the artist wants to convey. This research aims to find out the implied message that the artist wants to convey. Another aim is to find out the various visual elements in the painting. The unique Wounded Deer painting definitely has a deep meaning. The method in this research uses the Feldman model of formalistic criticism which focuses on the visual elements in a work. This method was chosen because it only examines the visual work without involving the artist or existing phenomena. The results of this research are in the form of an explanation based on the stages of formalistic criticism, including: work description, formal analysis, interpretation, and evaluation.